Implementation of the Flipped Classroom Learning Method in Rural Areas - Yohanis Banamtuan; Desy Prima; Delvi Selvia; Hartono Udon; Indri Sri Devi Br. Sembiring (Jurnal Pendidikan Agama Kristen (JUPAK), 2025)
The flipped classroom method is a very effective learning method applied in emergency conditions such as the pandemic that has just passed. However, in general, this flipped classroom method is only applied to schools in urban areas because of the very supportive facilities such as strong internet networks, other electronic facilities such as computers, laptops, smart phones and so on. While the condition of schools with various limitations of internet networks, electricity, computers, laptops and smart phones is very difficult in the application of this flipped classroom learning method. That is why the researchers agreed to discuss the implementation of the flipped classroom method especially for schools in rural areas. Various limitations owned by rural schools often hamper the teaching and learning process so that learning objectives cannot be realized properly. The purpose of this study is to present practical steps in the teaching and learning process using the flipped classroom method in rural areas, find the obstacles and solutions so that it can help teachers and students in rural areas. The method used in this research is qualitative with a library study approach. The result of the research on the implementation of flipped classroom method in rural areas is that the flipped classroom method can be implemented in rural areas with all its limitations and constraints.